El cultivo de la yuca en Ecuador - Hinostroza G., F.O. (International Center for Tropical Agriculture, 1991)
Different aspects of cassava cultivation in Ecuador are described, namely agroclimatic regions, climate, soils, production areas, production systems, main var. grown in production zones, and uses. Among the main production constraints are the irregular rainfall patterns, the lack of marketing studies, and inadequate transfer of technology. The Instituto Nacional de Investigaciones Agropecuarias modified the technology recommended by CIAT, adapting it to Ecuadorian conditions; 9 genotypes have been introduced and are currently adapted under greenhouse conditions; transfer to the field is pending. Regional trials have been carried out in Quevedo, Santo Domingo, Napo, and Loja with introduced var. and hybrids and local material. The infrastructure for international germplasm exchange is still inadequate. Future plans include the collection of local material and assessment of characteristics as well as the improvement of major cassava production and utilization systems in Manabi Province. (CIAT)